Thematic Qur'anic Interpretation of Human Trafficking: An Analysis of QS An-Nur 33 and QS Yusuf 19–20 within the Framework of Islamic Ethics and the Palermo Protocol - Wara, Jullul; Maram, Ahmad Nabilul; Fattah, Abdul (Jurnal Ushuluddin, 2025)
This study explores the Qur’anic perspective on human trafficking through a thematic analysis of QS An-Nur 33 and QS Yusuf 19–20. The objective is to interpret the linguistic meanings of al-bighāʾ, syarā, and milk al-yamīn, and to map their alignment with the tripartite definition of the Palermo Protocol in order to formulate an Islamic ethical framework for combating trafficking. The research employs a qualitative library research method, integrating classical and contemporary tafsir (Ibn Kathir, al-Maraghi, Quraish Shihab) with human rights literature. Linguistic analysis reveals that the three Qur’anic terms represent the act, means, and purpose of modern exploitation. The interpretation of QS An-Nur 33 emphasizes the prohibition of forced prostitution and the protection of women's dignity, while the interpretation of QS Yusuf 19–20 critiques child commodification and highlights the trauma experienced by victims. Mapping these interpretations onto the Palermo Protocol uncovers a complete correspondence with the elements of act, means, and purpose, thereby reinforcing the legitimacy of Sharia in criminalizing trafficking. The synthesis of the values of ʿadl (justice), raḥmah (compassion), and karāmat al-insān (human dignity) generates an ethical paradigm that underpins legislation, faith-based advocacy, and rehabilitation programs. The findings affirm that the Qur’an not only aligns with but also enriches the international legal framework with spiritual motivation. Practical implications include issuing fatwas equivalent to ḥirābah, allocating zakat for victims, and developing anti-trafficking education curricula